2012
DOI: 10.5296/jfs.v1i1.1947
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Some Selected Garri Samples Sold in Lagos Metropolis

Abstract: Three samples of different kinds of white garri were purchased from, Mushin, Shomolu and Yaba market in Lagos. A reference sample of garri was produced in Yaba College of Technology processing Laboratory. The samples were coded as AOU, BRT, CBN and REF (for the reference). Proximate analysis showed that moisture content ranged between 8-10%, carbohydrate 87-85%, protein 1-3%, fats content 0.5-0.7%, crude fibre 0.5-0.8%, ash content 1-3%. The physiochemical properties of the samples showed that bulk density var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
3
4
0
Order By: Relevance
“…It has been reported that the less fibrous a gari is, the better the quality (Sanni, Adebowale, Awoyale, & Olatunde, ). The crude fiber content recorded for the gari samples were close to the range of values (0.55%–0.71%) reported by Okolie, Brai, and Afoyebi ().…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…It has been reported that the less fibrous a gari is, the better the quality (Sanni, Adebowale, Awoyale, & Olatunde, ). The crude fiber content recorded for the gari samples were close to the range of values (0.55%–0.71%) reported by Okolie, Brai, and Afoyebi ().…”
Section: Resultssupporting
confidence: 87%
“…And this implies that the toasting variables did not have any significant ( p > 0.05) effect on pH of the gari samples. The pH values of the gari samples were close to the range of values of 6.4–6.6 reported by Okolie et al () but higher than the values of 3.58 to 4.21 reported by Apea‐Bah, Oduro, Ellis, and Safokantanka ().…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The moisture content in the gari samples was lower than that of the commercial gari (16.60%). Indeed, it is reported that the high moisture content implies that a gari sample will not have a good storage potential [ 38 ], while the values obtained from gari samples of this study were good compared to those reported by Okolie et al [ 39 ] for good storage potential and quality as well as those recommended by Oduro et al [ 40 ]. The gari should be properly dried to a possible very low moisture content.…”
Section: Discussionsupporting
confidence: 66%
“…The carbohydrate content obtained from white garri from market D had the highest value of 80.37 % among all the garri samples tested during this study. However, a higher carbohydrate content of 85.8 % was reported by Okolie et al (2012), from garri samples sold in Lagos metropolis, Nigeria. The difference in the carbohydrate content might be due to the preliminary loss of soluble carbohydrate in the previous unit processing of the cassava tubers.…”
Section: Resultsmentioning
confidence: 99%